1-La solució de l'equació: 9x+5=x-3 és: x=
2-La solució de l'equació, 3(5-2x)-3= -2(x-10)és: x=
3-La solució de l'equació, x-3(2x+3)= 2(3-2x)-12 és: x=
4-La solució de l'equació, 8(x+2)-10= 3(2x-1)+9és:x=
5-La solució de l'equació, 3x-4(1-x)=4+5x és:x=

1

Respuestas

2013-10-07T20:35:58+02:00
1- 9x+5=x-3 és: x=
    9x - x = -3 - 5
          8x = -   8                x = - 1

2- 3(5-2x)-3= -2(x-10)és: x=
    15 - 6x - 3 = - 2x +20
         - 7x + 2x = - 12 + 20
                  - 5x = 8                    x = - 8/5
 
3- x-3(2x+3)= 2(3-2x)-12 és: x=
    x - 6x - 9 = 6 - 4x - 12
    x - 6x + 4x = 6 -12 + 9
                 - x = 3                    x = - 3

4- 8(x+2)-10= 3(2x-1)+9és:x= 
    8x + 16 - 10 = 6x - 3 +  9
              8x - 6x = - 3 +  9  - 16 +  10
                    2x = 0                 x = 0

5- 3x-4(1-x)=4+5x és:x=
    3x - 4 + 4x = 4 +  5x
    3x + 4x -  5x = 4 + 4
                 2x = 8            x = 4